Pengaruh Corporate Risk dan Leverage terhadap Tax Avoidance - Safii, Mohamad; Sahara, Lita (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study aims to analyze and test the corporate risk and leverage to tax avoidance. The type of research used in this study is a type of quantitative research with a causal associative approach, and the source used is secondary data in the form of annual reports on coals sector for 5 (five) periods. The population in this study were companies in the coals sector listed on the Indonesia Stock Exchange during 2018-2022 and there were 43 companies. The research sample was selected based on purposive sampling technique by obtaining 14 companies for 5 periods or 70 observation data. To test the hypothesis using the program EViews series 9. Data were analyzed using the method of panel data regression analysis. The results of this study partially show that corporate risk have an effect to tax avoidance, meanwhile leverage had no effect to tax avoidance. Simultaneously show that corporate risk and leverage have an effect to tax avoidance.